ASSOCIATION BETWEEN SERUM 25-HYDROXYVITAMIN D LEVELS AND VITAMIN D RECEPTOR POLYMORPHISMS IN HIV-INFECTED CHILDREN - SUFIAWATI, IRNA; SAPATARINI, RISTI; RIYANTI, ERISKA; MAULANI, INTAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The clinical and genetic evidence is accumulating that vitamin D may play a role in modulating human immunodeficiency virus (HIV) infection. The aim of this study was to evaluate serum 25-hydroxyvitamin D [25(OH)D] levels in HIV-infected children and its association with vitamin D receptor (VDR) gene Bsml and Fokl polymorphisms. Methods: Serum 25(OH)D levels were measured using 250HD Liaison XL®. The VDR genes were detected by CLART®MetaBone. Results: This study included 34 HIV-infected children on highly active antiretroviral therapy (HAART) for more than a year, aged 6-14 y. The results revealed that the mean of serum 25(OH)D levels were 19.6±7.0 nmol/l. The mean of CD4+T-cell counts was 724 (18–1805) cell/mm3 and CD4 % was 23.72±10.77. The genotypic frequency Bsml and Fokl polymorphisms in HIV-infected children were BB 29%, Bb 41%, bb 29% and FF 47%, Ff 44%, ff 9%, respectively. Serum 25(OH)D levels were associated with Bsml polymorphisms (p<0.05), but not with Fokl polymorphisms (p>0.05). Conclusion: The present study showed that vitamin D deficiency is common in HIV-infected children, and genetic variant could lead to altered activity of vitamin D. Therefore, it is important to consider vitamin D status routinely in preventing the development of opportunistic infections and supplementation of vitamin D is warranted among HIV-infected children on HAART.